Daniel Carroll papers - Carroll, Daniel, 1764-1849.
Correspondence, financial and legal documents, surveys of plats, newspaper clippings, and other papers pertaining primarily to Carroll's business interests and to his real estate holdings in what later became the Capitol Hill area of Washington, D.C. Includes material on land surveying and sales in Washington, D.C., and Baltimore, Md.; collection of rents; Carroll's holdings in Baltimore Iron Works and Hockley Forge; the settlement of Carroll's estate by his daughters, Ann C. Carroll and Maria Carroll Fitzhugh; and Pierre Charles L'Enfant's partial wrecking of Carroll's residence, Duddington Manor, a factor in L'Enfant's break with the commissioners of Washington, D.C. Correspondents during Carroll's lifetime include Richard Brent, William Leigh Brent, Charles Carroll of Bellevue (d. 1820), Charles Carroll of Carrollton (1737-1832), Daniel Carroll of Rock Creek (1730-1796), Thomas Emory, James Greenleaf, William Alexander Hammond, Christopher Johnson, and John Merryman. Later correspondents include George F. Appleby, Ann C. Carroll, Richard H. Clarke, John Sterrett Gittings, William Alexander Gordon, William Hickey, James Birdseye McPherson, and Thos. E. Waggaman.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Landowner and businessman of Washington, D.C. Known as Daniel Carroll of Duddington.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Appleby, George F. -- Correspondence; Brent, Richard, -- 1757-1814 -- Correspondence; Brent, William Leigh, -- 1784-1848 -- Correspondence; Carroll, Ann C; Carroll, Ann C. -- Correspondence; Carroll, Charles, -- 1737-1832 -- Correspondence; Carroll, Charles, -- -1820 -- Correspondence; Carroll, Daniel, -- 1730-1796 -- Correspondence; Clarke, Richard H. -- 1827-1911 -- Correspondence; Emory, Thomas, -- 1782- -- Correspondence; Fitzhugh, Maria Carroll; Gittings, John Sterrett -- Correspondence; Gordon, William Alexander, -- -1873 -- Correspondence; Greenleaf, James, -- 1765-1843 -- Correspondence; Hammond, William Alexander, -- 1828-1900 -- Correspondence; Hickey, William, -- 1798-1866 -- Correspondence; Johnson, Christopher, -- active 19th century -- Correspondence; L'Enfant, Pierre Charles, -- 1754-1825.; McPherson, James Birdseye, -- 1828-1864 -- Correspondence; Merryman, John, -- 1824-1881 -- Correspondence; Waggaman, Thos. E. -- Correspondence; Carroll family; Baltimore Iron Works (Baltimore, Md.); Duddington Manor (Washington, D.C.); Hockley Forge; Iron industry and trade -- Maryland; Real property -- Maryland -- Baltimore; Real property -- Washington (D.C.); Rent; Baltimore (Md.) -- Surveys; Capitol Hill (Washington, D.C.); Washington (D.C.) -- History; Washington (D.C.) -- Surveys; Businessmen; Landowners